2015
DOI: 10.1016/j.ijid.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Exploring HIV infection and susceptibility to measles among older children and adults in Malawi: a facility-based study

Abstract: We found no evidence that HIV infection contributes to the risk of measles infection among adults, but HIV-infected children (including at ages older than previously reported), were less likely to be seroprotected in this sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Other reports have shown that HIV infection is associated with greater severity of measles disease, higher mortality and prolonged measles virus shedding (Polonsky et al 2015).…”
Section: Measlesmentioning
confidence: 95%
“…Other reports have shown that HIV infection is associated with greater severity of measles disease, higher mortality and prolonged measles virus shedding (Polonsky et al 2015).…”
Section: Measlesmentioning
confidence: 95%
“…A facility-based study was conducted to assess differences in levels of measles antibodies between HIV-infected and uninfected individuals in Chiradzulu district, Malawi [6]. A secondary objective of this study was to correlate self-reported measles protective status with measles serological result.…”
Section: Methodsmentioning
confidence: 99%
“…As part of a larger study on measles serological protection in HIV infected and uninfected individuals in Chiradzulu district [6], we collected data on measles vaccination and disease history. Our aim was to explore self-reported measles protective status, and comparing this with measles serological result, in order to inform local assessments of vaccine coverage and provide important guidance on how these assessments could be improved to ensure control strategies are successful.…”
Section: Introductionmentioning
confidence: 99%